Evaluation of the Impact of Body Mass Index on Tooth Development, Tooth Eruption and Dental Caries Formation in Childhood: A Cross-sectional Study - Betül Memiş Özgül; Didem Sakaryalı Uyar (Ankara University, 2023)
Purpose: The aim of this cross-sectional study was to evaluate the impact of different body mass index status on dental caries, tooth development, and tooth eruption regarding the development of dental tissues and dental health problems. Materials amp; Methods: One-hundred-seventy-six children, aged between 3-12 years old, were included in the study and distributed into 4 groups (n:44) according to their body mass index as underweight, healthy, overweight, and obesity. Data on tooth development, tooth eruption, and dental caries were recorded by using modified Demirjian, Carvalho, and decayed-missing-filled-tooth (DMFT), respectively. According to the obtained data, p lt;0.05 was accepted as significant. Results: According to the results, DMFT was significantly higher in children with underweight than overweight and obesity whereas, whereas earlier tooth eruption was seen in children with healthy and obesity than underweight (p lt;0.05). Also, there was a significant difference between the groups in terms of DMFT (p lt;0.05). Conclusion: Dental caries was higher in children with malnourishment while tooth eruption was earlier in children with obesity. Therefore, general practitioners or pediatricians should be aware of the oral effects of obesity or malnutrition and consult a pediatric dentist.